Physical Characteristics of Water to Indicate and Improve Gonad Development of Climbing Perch (Anabas testudineus) in Peat Swamp Habitats - Bungas, Kartika; Elvience, Rosana; Rosita, Rosita; Ashari, Fadhil Muhamad (Jurnal Perikanan Universitas Gadjah Mada, 2025)
Peat swamps are aquatic ecosystems that have distinctive physicochemical characteristics that can affect fish life, including the Climbing perch (Anabas testudineus). This study aims to analyse the physics of water and gonad maturity of Climbing Perch in peat swamps, to understand the relationship between environmental conditions and the reproductive cycle of Climbing Perch species (Anabas testudineus). The water physics parameters measured included temperature, brightness, depth, and Total Dissolved Solid (TDS), which were compared with the Gonad Maturity Level of Climbing perch caught from the research stations (Station-1, Station-2, and Station-3) in Tanjung Taruna peat swamps. The results showed that the physical parameters of the waters play an important role in the reproduction of the Climbing Perch (Anabas testudineus). Variations in temperature, brightness, depth, and TDS affect metabolism and the hormonal system that regulates gonadal development. Optimal temperature promotes the secretion of reproductive hormones, while extreme temperatures inhibit gonad maturation. Brightness and depth affect eating activities, physiological comfort, and stress levels that impact energy allocation for reproduction. TDS ideally maintains osmotic balance, while high TDS reduces energy for gonadal development and spawning success.